Search for Randall-Sundrum gravitons in dilepton and diphoton final states. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2005)
We report the first direct search for the Kaluza-Klein (KK) modes of Randall-Sundrum gravitons using dielectron, dimuon, and diphoton events observed with the D0 detector operating at the Fermilab Tevatron pp(-) Collider at sqrt[s]=1.96 TeV. No evidence for resonant production of gravitons has been found in the data corresponding to an integrated luminosity of approximately equal to 260 pb(-1). Lower limits on the mass of the first KK mode at the 95% C.L. have been set between 250 and 785 GeV, depending on its coupling to standard model particles.